2016
DOI: 10.3389/fnhum.2016.00620
|View full text |Cite
|
Sign up to set email alerts
|

Are Modular Activations Altered in Lower Limb Muscles of Persons with Multiple Sclerosis during Walking? Evidence from Muscle Synergies and Biomechanical Analysis

Abstract: Background: Persons with Multiple Sclerosis frequently have gait deficits that lead to diminished activities of daily living. Identification of motoneuron activity patterns may elucidate new insight into impaired locomotor coordination and underlying neural systems. The aim of the present study was to investigate muscle synergies, identified by motor modules and their activation profiles, in persons with Multiple Sclerosis (PwMS) during walking compared to those of healthy subjects (HS), as well as, exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 72 publications
6
50
0
Order By: Relevance
“…Second, some synergies were not altered in weights but instead, ceased to be used strongly in patterns. Both of these types of changes are likely significant in motor drive infrastructure, pattern generation, and the pathologies and injury effects where synergies may have impact (27,(33)(34)(35)(36)(37)(38)(39)(40)(44)(45)(46)(47)(48)(49). Synergies normally weakly activated in intact CNS that become active in disease would interfere with normal function and be pathological.…”
Section: Discussionmentioning
confidence: 99%
“…Second, some synergies were not altered in weights but instead, ceased to be used strongly in patterns. Both of these types of changes are likely significant in motor drive infrastructure, pattern generation, and the pathologies and injury effects where synergies may have impact (27,(33)(34)(35)(36)(37)(38)(39)(40)(44)(45)(46)(47)(48)(49). Synergies normally weakly activated in intact CNS that become active in disease would interfere with normal function and be pathological.…”
Section: Discussionmentioning
confidence: 99%
“…37 However, the participant pool represents a large range of walking functions and disability levels (EDSS score = 2.5-6.5), and measures of walking endurance and speed in the present study are similar to those previously reported for men and women with MS. 26,27 The medial gastrocnemius muscle was evaluated in the present study because of the critical role of this muscle in ambulation and its association with gait parameters. 38,39 Yet, note that many other lower extremity and trunk muscles contribute to ambulation, 39 and relationships between muscle function and walking ability may vary if assessed in different lower extremity muscles. In addition, muscle strength was evaluated during voluntary contractions, which can be influenced by both central and peripheral factors, so the observations related to strength cannot be solely attributed to peripheral mechanisms associated with skeletal muscle dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle synergies during walking are generally extracted from a few gait cycles ranging from 1 ( Steele et al, 2015 ; Lencioni et al, 2016 ) to 20 gait cycles ( Kim et al, 2016 ). In most cases, synergies are computed by averaging or concatenating around 10 gait cycles ( Ivanenko et al, 2003 , 2004 ; Monaco et al, 2010 ; Chvatal and Ting, 2012 ; Coscia et al, 2015 ; Haghpanah et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%